Testing an adherence‐improving app for patients with psoriasis. (2nd November 2018) - Svendsen, M.T.; Andersen, F.; Andersen, K.H.; Pottegård, A.; Johannessen, H.; Möller, S.; August, B.; Feldman, S.R.; Andersen, K.E.
Summary: Psoriasis is a common chronic inflammatory skin disease which causes red, scaly plaques (patches of skin), often on the knees, elbows, scalp and trunk. Psoriasis can have a negative impact on patients' quality of life, and additionally creates a 'socioeconomic burden' due to healthcare costs, time off work, etc. Topical calcipotriol with corticosteroids are a recommended first treatment of mild‐to‐moderate psoriasis, but many patients ‐ for many different reasons ‐ do not apply the creams or ointments as prescribed. This study investigated if the use of a patient‐supporting applications for smartphones (apps) could improve patients' use of a topical (applied to the skin) drug (calcipotriol/betamethasone dipropionate combination in a cutaneous foam) and in addition reduce severity of psoriasis and improve quality of life short‐ and long‐term. Danish dermatologists conducted a trial at a dermatology clinic at Odense University Hospital in Denmark. 134 patients were included and allocated to either use the drug (66 patients) or to use the drug together with support from an app (68 patients) for a 4‐week period. The app provided once‐daily compulsory treatment reminders and was also able to monitor if patients were using their medication, through an electronic‐monitor chip mounted on top of the foam dispenser. The information was synchronized via Bluetooth® to the patient's smartphone. 91% of the patients returned for all follow‐up visits during a half‐year period. This controlled trial showed that patients using the app significantly improved use of the medication in the 4‐week period and had a short‐term reduction in severity of psoriasis. The authors concluded that apps have potential to improve psoriasis patients' use of topical medications. Abstract : Linked Article: Svendsen et al. Br J Dermatol 2018; 179 :1062–1071